PEMANFAATAN Calotropis gigantea SEBAGAI PENGOBATAN DINI BOROK GANGREN UNTUK PREVENTIF AMPUTASI PADA DIABETES MELITUS: LITERATURE REVIEW - Salsabiella, Elok; Dina Anggraeni, Amaliyah (School of Pharmacy Institut Teknologi Bandung, 2025)
Gangrenous ulcers due to diabetes increase the risk of amputation. Madurese herb Calotropis gigantea is empirically known to accelerate wound healing through its anti-inflammatory, antioxidant, and angiogenesis-stimulating activities, as well as helping to inhibit infection and repair tissues. To determine the effectiveness of traditional Madurese herb based on Calotropis gigantea extract as a complementary therapy in accelerating the healing of gangrenous ulcers in patients with diabetes mellitus. Using Systematic Literature Review (SLR) based on google scholar database, PubMed, and ScienceDirect for the period 2020-2025 indexed by SCImago Journal Rank (SJR) Quartile 1 - 2 articles were selected based on inclusion and exclusion criteria. Medical Subject Heading (MeSH) was used as a reference for literature search keywords with the use of the PIO (Problem, Intervention, Outcome) concept as an extraction and analysis of research articles. The results showed that Calotropis gigantea extract has anti-inflammatory, antioxidant, and angiogenesis-stimulating activities, which effectively accelerate the healing of gangrenous ulcers and reduce the risk of serious complications. The bioactive compounds in this Madurese herb support tissue regeneration and infection control. Traditional Madurese herb based on Calotropis gigantea extract has the potential to be an effective complementary therapy to support conventional treatment, reduce the risk of amputation, and improve the quality of life of patients with gangrenous ulcers due to diabetes.